The Effect of Temperature on the Destruction of Salmonellas in Activated Sludge - Yaziz, Mohammad Ismail (1985)
The effect of temperature on the survival of salmonellas in activated sludge was examined. The results showed that the Salmonella destruction rates increased in line with increasing temperature of the mixed liquor from 5° to 25°C, whereas at 30°C the rate declined markedly. This is most probably due to inactivation of ciliate protozoa at the higher temperature resulting in increased survival of the pathogens. The slow reduction in the number of salmonellas at 30°C may be the result of nutrient starvation, in addition to other possible mechanisms such as the lytic action of bacterial viruses.